Hormone‐related diseases and prostate cancer: An English national record linkage study - Watts, Eleanor L.; Goldacre, Raphael; Key, Timothy J.; Allen, Naomi E.; Travis, Ruth C.; Perez‐Cornago, Aurora (International journal of cancer, 2020)
Insulin‐like growth factor‐I (IGF‐I) and testosterone may be related to prostate cancer risk. Acromegaly is associated with clinically high IGF‐I concentrations. Klinefelter's syndrome, testicular hypofunction and hypopituitarism are associated with clinically low testosterone concentrations. We aimed to investigate whether diagnosis with these conditions was associated with subsequent prostate cancer diagnosis and mortality. We used linked English national Hospital Episode Statistics and mortality data from 1999 to 2017 to construct and follow‐up cohorts of men aged ≥35 years diagnosed with (i) acromegaly (n = 2,495) and (ii) hypogonadal‐associated diseases (n = 18,763): Klinefelter's syndrome (n = 1,992), testicular hypofunction (n = 8,086) and hypopituitarism (n = 10,331). We estimated adjusted hazard ratios (HRs) and confidence intervals (CIs) for prostate cancer diagnosis and death using Cox regression in comparison with an unexposed reference cohort of 4.3 million men, who were admitted to hospital for a range of minor surgeries and conditions (n observed cases = 130,000, n prostate cancer deaths = 30,000). For men diagnosed with acromegaly, HR for prostate cancer diagnosis was 1.33 (95% CI 1.09–1.63; p = 0.005; n observed cases = 96), HR for prostate cancer death was 1.44 (95% CI 0.92–2.26; p = 0.11; n deaths = 19). Diagnosis with Klinefelter's syndrome was associated with a lower prostate cancer risk (HR = 0.58, 95% CI 0.37–0.91; p = 0.02; n observed cases = 19) and hypopituitarism was associated with a reduction in prostate cancer death (HR = 0.53, 95% CI 0.35–0.79; p = 0.002; n deaths = 23). These results support the hypothesised roles of IGF‐I and testosterone in prostate cancer development and/or progression. These findings are important because they provide insight into prostate cancer aetiology. What's new? Although the incidence rates of prostate cancer vary globally, little is known about modifiable risk factors. Previous studies have shown insulin‐like growth factor‐I (IGF‐I) and testosterone may be related to prostate cancer risk. Using national hospital admission data, the authors examined whether these associations are consistent across clinical extremes in comparison with a reference cohort. Men diagnosed with acromegaly (characterised by high IGF‐I) had an increased risk of incident prostate cancer, while men diagnosed with diseases characterised by low testosterone had a lower risk of prostate cancer mortality. The findings support the role of IGF‐I and testosterone in prostate cancer pathogenesis.